Digital Marketing, Social Media Marketing, dan e-WOM untuk UMKM Kota Binjai - Merry Moy Mita (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
The rapid acceleration of the digital economy has positioned Micro, Small, and Medium Enterprises (SMEs) at a strategic crossroads. This study investigates the impact of digital marketing and social media marketing on the performance of SMEs in Binjai, North Sumatra, while exploring the mediating role of Electronic Word of Mouth (e-WOM). Utilizing a quantitative approach with a sample of 182 SME owners, data were analyzed using multiple linear regression and path analysis via SPSS 26. The findings demonstrate that digital marketing and social media marketing initiatives significantly and positively influence business performance, accounting for 54.2% of the variance. Notably, social media marketing emerged as the most dominant predictor, fostering high levels of customer engagement. Furthermore, path analysis reveals that e-WOM serves as a critical mediator; effective social media strategies stimulate authentic digital testimonials, which subsequently enhance consumer trust and sales volume. This research concludes that for SMEs in emerging local markets like Binjai, the orchestration of digital reputation through e-WOM is fundamental to achieving sustainable competitive advantage in an increasingly volatile digital landscape.